1995
DOI: 10.1002/ijc.2910630617
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the probenecid‐sensitive transport of daunorubicin or calcein and the glutathione status of cells overexpressing the multidrug resistance‐associated protein (MRP)

Abstract: Cells exposed to calcein acetoxymethyl ester (calcein AM) in the growth medium become fluorescent following cleavage of calcein AM by cellular esterases to produce the fluorescent derivative calcein. It has previously been shown by others that multidrug resistant cells which overexpress P-glycoprotein accumulate much less fluorescent calcein than the corresponding parental cells. We have now examined the transport of calcein in multidrug resistant cells which overexpress an alternative transporter, the multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…Concerning the role of MRP1 and MRP2 in cytostatic drug resistance, it has been documented in several experiments that both proteins are able to transport unconjugated hydrophobic drugs and anions (Feller et al, 1995;Versantvoort et al, 1995;Holló et al, 1996), but GSH modifies this transport, most likely via a cotransport mechanism (Loe et al, 1996b(Loe et al, , 1998Deeley and Cole, 1997;Evers et al, 1998). In experiments to be reported elsewhere, we found that vinblastine and GSH produced a synergistic stimulation of the MRP2-ATPase (manuscript under preparation).…”
Section: Discussionsupporting
confidence: 59%
“…Concerning the role of MRP1 and MRP2 in cytostatic drug resistance, it has been documented in several experiments that both proteins are able to transport unconjugated hydrophobic drugs and anions (Feller et al, 1995;Versantvoort et al, 1995;Holló et al, 1996), but GSH modifies this transport, most likely via a cotransport mechanism (Loe et al, 1996b(Loe et al, , 1998Deeley and Cole, 1997;Evers et al, 1998). In experiments to be reported elsewhere, we found that vinblastine and GSH produced a synergistic stimulation of the MRP2-ATPase (manuscript under preparation).…”
Section: Discussionsupporting
confidence: 59%
“…The efflux of free calcein (the fluorescent form) is then determined after washing away excess calcein-AM. Whereas calcein AM is a substrate for MDR1 and MRP, calcein is not a substrate for MDR1, thus allowing specific MRP efflux activity to be determined (Versantvoort et al, 1995;Essodaigui et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…We have then quantified the functional expression of MRP-like activity with the fluorescent probe calcein (Versantvoort et al, 1995;Essodaigui et al, 1998) and probed for functional differences in MRP-like activities at apical and basal membranes with a range of pharmacological tools. T84 cells, a model of human colonocytes that lack MRP2 expression Simmons, 2001, 2002), are used in comparison.…”
mentioning
confidence: 99%
“…Nestin→ GAPDH→ (Versantvoort et al 1995). Thus, in P-gp-positive cells, the efflux activity of this transporter blocks calcein/AM entry and antagonizes the intracellular retention of fluorescent calcein.…”
Section: Mdr1→mentioning
confidence: 99%